Symmetrical Modular Optical Phased Array With Combined Spatial and Amplitude Modulation for Scalable Indoor Wireless Networks - Kosala Herath; Malin Premaratne; Sharadhi Gunathilake; Ampalavanapillai Nirmalathas (IEEE Open Journal of the Communications Society)
Scalable optical wireless networks are crucial to address the demand for ultra-broadband wireless connectivity in future workspaces and living environments. This study presents a novel theoretical framework for the dual-carrier modular optical phased array (MOPA) architecture, specifically tailored for indoor wireless communication networks. We introduce the non-uniform spherical wave (NUSW) model for a near-field analysis of electromagnetic radiation in a single-carrier MOPA, extending this to dual-carrier configurations. Our analysis demonstrates enhanced beam-focusing capabilities and significant suppression of grating lobes in the dual-carrier system. Expanding on this theoretical model, we perform a comprehensive numerical analysis of a dual-carrier MOPA system installed on a planar ceiling within an indoor room. To quantitatively assess grating lobe suppression, we propose a novel figure-of-merit (FoM) and compare the beam-focusing performance of both single- and dual-carrier MOPA systems. Furthermore, we introduce a new symmetrical excitation mechanism combined with spatial modulation for data symbol encoding within the MOPA architecture. Our results reveal that this approach provides high-level physical layer security (PLS) for wireless communication. By integrating amplitude shift keying (ASK) with spatial modulation, we evaluate the bit error rate (BER) against signal-to-noise (SNR) ratio across different symmetrical excitation scenarios. This evaluation demonstrates that our system achieves efficient digital signal communication with reduced complexity and robust performance under real-world noise conditions. Our findings advance the understanding of optical phased array systems and underscore their potential for secure, high-performance indoor wireless communication.